2006
DOI: 10.1152/japplphysiol.01031.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carbon dioxide on neonatal mouse lung: a genomic approach

Abstract: Despite the deleterious effects associated with elevated carbon dioxide (CO(2)) or hypercapnia, it has been hypothesized that CO(2) can protect the lung from injury. However, the effects of chronic hypercapnia on the neonatal lung are unknown. Hence, we investigated the effect of chronic hypercapnia on neonatal mouse lung to identify genes that could potentially contribute to hypercapnia-mediated lung protection. Newborn mouse litters were exposed to 8% CO(2), 12% CO(2), or room air for 2 wk. Lungs were excise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 52 publications
(55 reference statements)
1
29
1
Order By: Relevance
“…To investigate the molecular basis of the physiological effects of hypercapnia and identify CO 2 -responsive promoters to use as markers for dissecting CO 2 -signaling pathways, we performed microarray analysis on adult flies. Similar to the limited changes in gene expression seen in neonatal mice raised in CO 2 (47), exposure of adult flies to 13% CO 2 for 24 h causes fewer than 500 genes to be up-regulated or down-regulated Ͼ1.5-fold, and fewer than 10 by Ͼ10-fold. Importantly, the regulated genes define discrete physiological functions.…”
Section: Resultsmentioning
confidence: 74%
“…To investigate the molecular basis of the physiological effects of hypercapnia and identify CO 2 -responsive promoters to use as markers for dissecting CO 2 -signaling pathways, we performed microarray analysis on adult flies. Similar to the limited changes in gene expression seen in neonatal mice raised in CO 2 (47), exposure of adult flies to 13% CO 2 for 24 h causes fewer than 500 genes to be up-regulated or down-regulated Ͼ1.5-fold, and fewer than 10 by Ͼ10-fold. Importantly, the regulated genes define discrete physiological functions.…”
Section: Resultsmentioning
confidence: 74%
“…The high soil temperature at Furnas also presumably increases metabolic O 2 consumption and demand, adding a premium to improved trans-epidermal diffusion efficiency. The structural change in the gas permeable exchange surface of Amynthas seems to be functionally analogous to the thinning of alveolar epithelia observed in CO 2 -exposed neonatal mice compared with controls (Li et al, 2006).…”
Section: Morphometry and Cell Compositionmentioning
confidence: 63%
“…We have previously shown that chronic inhalation of CO 2 prevented PHT in chronic hypoxia-exposed neonatal rats (31), a model in which pulmonary inflammation is not apparent (47). Given the major putative role for lung inflammation in the pathogenesis of BPD (61,62,66) and evidence for anti-inflammatory effects of inhaled CO 2 (37,40,45,72), we were interested in examining the effects of therapeutic hypercapnia on an alternative rat model in which inflammation is a prominent early feature. The concentrations of CO 2 examined in bleomycin-exposed animals were intended to reproduce what are generally considered, in the clinical setting, to represent moderate (5% CO 2 ; mean elevation of Pa CO 2 15-20 mmHg) and severe (7% CO 2 ; mean elevation of Pa CO 2 35 mmHg) levels of hypercapnia.…”
Section: Discussionmentioning
confidence: 99%